Um estudo designativo em fronteiras enunciativas: a corrupção pelo prisma da semântica histórica da enunciação - Machado, Julio Cesar (Universidade Federal de São Carlos, 2010)
We propose to conduct a enuciative-semantic study on corruption in the brazilian enunciation space. Affiliated ourselves to Historical Semantic of Enunciation as a way to understand the meaning, and to the Semântica do Acontecimento as a way to investigate data. By scanning the functioning of corruption in ways atypical, our inquiries reveal corruption as a boundary object enunciation (of senses crime / non-crime) from a society composed of mixed social positions, no longer absolute, as the subject innocent-guilty or the responsible-irresponsible. However, to operate an adjacent region of oscillating directions from the inset of voices spoken by speakers mixed, would require a theoretical foundation capable of accessing thicknesses language between evident dimensions of the exact and apparent of the inexact. We propose, from the Russian language, an uplift device analysis unprecedented we call the teoria da agitação enunciativa. Through it, we can handle the corruption as built by a statement of evidence, while it is destroyed by an enunciation of appearance. We investigate documents that attempt to crystallize senses of corruption, the legal space of enunciation and the Final Report of the Work of CPMI "Postal" (mensalão case). These clippings sets up a scenario of agitation enunciative among mensalão X loan, mostly. We will see that by stating, Talker judge dilutes the political (issue) through legal, closing the senses of corruption. We'll also see that the law allows corruption. We will verify it works today: 1) a legal corruption, given by utterances of evidence, and guiding directions for corruption (crime), from places absolute (E-guilty), 2) and non-legal corruption, given by the utterances appearance, and guiding directions for pro-corruption (between crime and non-crime), from places inset (Efloating). Our work instigates a scientific practice more consistent with the present modern, overwhelming places an absolute mathematically regular society, which is still an imaginary but not working well, and develop mechanisms to deal with unusual thickness of the language. Making semantics along the lines we propose in this paper is to debunk the simplistic way of finding directions and be bothered by this mode at the same time. It examines breakdowns in utterances on corruption and bring about change in treaty relations. It destabilizes domestications of corruption in the canonical way of thinking of society.
A designating study in enunciative boundaries: corruption through the prism of the historical semantic of the utterance
Keywords: Semântica; Enunciação; Semântica argumentativa; Política - corrupção; Mensalão; Semantic; Utterance; Argumentation; Corruption; Mensalão; LINGUISTICA, LETRAS E ARTES::LINGUISTICA